Assessing E-Government User Satisfaction With Delone & Mclean Is Success Model And Digital Literacy - Hasbah, Nur Ilmi; Purwanto, Agus Joko; Rulinawaty, Rulinawaty (Universitas Muhammadiyah Mataram, 2025)
This study aims to analyze e-government user satisfaction using the D&M IS Success Model. Digital literacy is added as an additional variable to provide a broader explanation of the contradictory research results from previous studies. A quantitative research approach is employed. Research data were collected by distributing an online questionnaire to users of the BPS-Statistics Sulawesi Barat Province official e-government website who accessed the site in the last year. Multiple linear regression is used to analyze the impact of system quality, information quality, service quality, and digital literacy on user satisfaction, both partially and simultaneously, using RStudio. Findings indicate that the variables from the D&M IS Success Model have a significant influence on user satisfaction. On the contrary, digital literacy was found not to significantly influence user satisfaction when tested partially. Simultaneously, the four variables have a significant influence on user satisfaction. The R-squared value indicates that system quality, information quality, service quality, and digital literacy collectively explain 75.26% of user satisfaction. In comparison, the other 24,26% is covered by different variables that are not included in this research. These results offer valuable insights for governments implementing e-government websites to enhance user satisfaction and deliver improved public services. The study contributes to the existing literature on user satisfaction with e-government in Indonesia.